The Dynamics of a Predator-Prey Model Involving Disease Spread In Prey and Predator Cannibalism - Ah, Nurul Imamah; Kusumawinahyu, Wuryansari Muharini; Suryanto, Agus; Trisilowati, Trisilowati (Jambura Journal of Biomathematics (JJBM), 2023)
In this article, dynamics of predator prey model with infection spread in prey and cannibalism in predator is analyzed. The model has three populations, namely susceptible prey, infected prey, and predator. It is assumed that there is no migration in both prey and predator populations. The dynamical analysis shows that the model has six equilibria, namely the trivial equilibrium point, the prey extinction point, the disease free and predator extinction equilibrium point, the disease-free equilibrium point, the predator extinction equilibrium point, and the coexistence equilibrium point. The first equilibrium is unstable, and the other equilibria conditionally local asymptotically stable. The positivity and boundedness of the solution are also shown. The analytical result is supported by numerical simulation. It is shown that in such a high cannibalization the coexistence equilibrium is locally asymptotically stable.